Synthesis of C-2 methylene glycosides from C-2 propargyloxymethyl glycals exploiting the alkynophilicity of AuCl3 - Kashyap, Sudhir; Vidadala, Srinivasa Rao; Hotha, Srinivas (Tetrahedron Letters, 2007)
C-2 Methylene glycosides were synthesized from C-2 propargyloxymethyl glycals in a stereoselective manner using a catalytic quantity of AuCl3. The Au-catalyzed reaction was explored using various aglycones. The current protocol enables the preparation of C-2 methylene glycosides, tolerates diverse functional groups and is fast, catalytic and mild. (c) 2007 Elsevier Ltd. All rights reserved.
21st Carbo Symposium 2006, Univ Delhi, Delhi, INDIA, NOV 26-29, 2006